Comparing the hamstring muscle activity between injured and non-injured sides during a variety of Nordic hamstring exercises - Taspol Keerasomboon; Parunchaya Jamkrajang; Weerawat Limroongreungrat; Thammanunt Chrunarm; Toshiaki Soga; Norikazu Hirose (PLoS ONE, 2025)
Objectives To compare the electromyographic activity of the Biceps femoris long head and Semitendinosus muscles during bilateral and unilateral isometric Nordic hamstring exercise performed on an inclined platform at different knee flexion angles between leg side with and without a history of hamstring strain injury. Methods Ten physically active male volunteers with a history of hamstring strain injury in either leg performed isometric Nordic hamstring exercise, maintaining the exercise position for 5 s under the following conditions: (1) bilateral, 150° knee angle on a 50° inclined platform (BL50); (2) bilateral, 140° knee angle on a 40° inclined platform (BL40); (3) unilateral, 150° knee angle on a 50° inclined platform (UL50); and (4) unilateral, 140° knee angle on a 40° inclined platform (UL40). External torque on the knee joint was controlled to ensure equivalence across conditions. Electromyographic activity of the Biceps femoris long head, Semitendinosus, and related muscles was measured in both legs with and without a history of hamstring strain injury. Results The Biceps femoris long head muscle demonstrated significantly higher electromyographic activity during the unilateral Nordic hamstring exercise tasks, irrespective of hamstring strain injury history (p < 0.05). The Biceps femoris long head electromyographic activity was higher than Semitendinosus activity only in unilateral Nordic hamstring exercise conditions.. Additionally, no significant differences in the electromyographic activity were observed across the different slope angles when the external torque at the knee joint was matched (p > 0.05). Conclusions These findings suggest that performing isometric unilateral Nordic hamstring exercise at shallow knee flexion angles preferentially enhances the muscle activation of biceps femoris long head muscle regardless of hamstring strain injury history.